Deterministic and stochastic simulation for equipmet sizing and selection and for selecting surface mining alternatives - Ortiz Sánchez, Oswaldo (2007)
Mine equipment selection is a complex task due to numerous technical, geometrical and economical variables involved. The variety of equipment manufacturers and agents carrying different models, types and sizes make the selection procedure even more complex. The mine planner does not have a tool to correctly select the equipment or fl eet for a project. Simulation fi lls the gap and contributes to this goal. This study tries to apply deterministic and probabilistic simulation approaches in selecting mining equipment using fi eld data from two surface mine operations. The deterministic model uses a one year production plan from a quarry. The equipment fl eet is selected on the basis of minimum unit cost for both drilling and excavation-haulage equipment fl eets. For the probabilistic approach the GPSS language is applied. Programs were prepared for various combinations of loaders and haulers and data from a metallic open pit mine was processed. The optimum fl eet was selected by combining minimum cost per ton mined and maximum production tonnage per time unit.